Spring cum rain water harvesting and water budgeting of farm tank for growing vegetables crops in terrace land - KUMAR, JITENDRA; PANDEY, SURESH CHANDRA; NATH, SHYAM (Journal of Soil and Water Conservation, 2026)
A field experiment was conducted to assess the spring water harvesting in polylined farm tank 46 m3 and its effective utilization for vegetable crop production in 0.34 ha area under gravity fed drip and surface irrigation system at Experimental farm of ICAR-VPKAS, Almora. The selected vegetable crops (Tomato, Capsicum, Okra, French Bean, Chilli, Vegetable Pea, Cabbage, Broccoli and Kidney Bean) were grown under terrace condition during kharif, Rabi and Zaid season for assessment of water budgeting of spring-fed polylined tank. The water requirement of selected crops were estimated using CROPWAT ver 8.0 model under drip and surface irrigation was 749.54 m3 and 1274.15 m3 respectively. The digital water meter installed at site for measurement of spring water for irrigation on real time basis. On the basis of mean annual rainfall of Hawalbagh, Almora, maximum runoff cum spring water available annually for irrigation was 1759 m3 and shortage of water for crop irrigated through gravity fed drip system was 118.5 m3 and 66.9 m3 in April and May month respectively. The study revealed that auxiliary water harvesting tank 250 m3 required at site for store rain and spring cum runoff water and irrigate 0.11 ha area additionally in terms of selected crops grown at site under drip irrigation system. The saving of water 41.2 % were obtained under gravity fed drip irrigation compare to surface irrigation. The highest irrigation water productivity i.e. 20 kg/m3 in tomato crop followed by 16.33 kg/m3 for cabbage crop under gravity fed drip irrigation system.